Antropología jurídica, costumbre y pluralismo jurídico : una mirada a la sentencia que reconoció a la Amazonía como sujeto de derechos en Colombia (2020)
This monograph gathers the key theoretical discussions around custom and legal pluralism in legal anthropology. It emphasizes in Latin American Legal Anthropology. Literature review contributes to the discussion of custom as a source of law in the Latin American legal system. The text explores the role of custom in common law and questions it in civil law to argue that local, community and peripheral norms are still outside the margins of state legality. As a study case, it analyzes Colombian Supreme Court of Justice's Judgment 4360, which indicated in 2018 that the Amazon is subject to rights and a legal entity, in order to protect it from the deforestation. n this example, effective for 2020, the orders of a high court are shown as an expression of the state's will that displaces local custom to the limits of legality. Local actors interact with their own understanding of the laws, generating community norms. This, although it is interwoven with state norms and reflects a form of legal pluralism, for anthropologists and some legal theorists, is not fully recognized by the state because it is on its margins. Community norms shape local life and vice versa, in the sense that they offer the development of alternative understandings of norm and sovereignty